Student Perceptions of Assessment Practices in High School Social Studies: Implications for Teaching and Learning - Eka Yuliana Rahman; Amri Dhimas Maulana (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2024)
This study aims to explore students' perceptions of assessment practices in social studies subjects consisting of Economics, Geography, History and Sociology at SMAN 2 Tanggul and their implications for teaching and learning. Using a qualitative case study approach, this research collected data through in-depth interviews and classroom observations. A total of 30 students from grades X, XI, and XII were purposively selected to ensure the diversity of their experiences and views. The results showed that students tend to favour formative assessments that provide constructive feedback and opportunities to improve over summative assessments that are often perceived as adding pressure. Positive perceptions of formative assessment were associated with increased motivation to learn and active participation in class. In contrast, negative perceptions of summative assessments that are perceived as unfair and overly pressurised negatively impact student motivation and confidence. This research reveals that diverse and innovative assessment practices are needed to accommodate students' learning needs more effectively. The implications of these findings emphasise the importance for teachers to develop assessment strategies that are fair, useful and responsive to students' needs, which can ultimately improve the quality of teaching and learning outcomes in social studies classes.